The Responsive Judge International Perspectives (Ius Gentium: Comparative Perspectives on Law and Justice,, 2018)
This book focuses on the changing role of judges in courts, tribunals, and other forums across a variety of jurisdictions. With contributions by international experts in judicial administration and senior judicial figures, it provides a unique comparative perspective on the role of modern judges in a rapidly evolving environment and the pressures of effective judicial administration. The chapters are sourced from a Collaborative Research Network focused on innovations in judging, and sponsored by the international Law and Society Association. The book provides essential insights and perspectives for judges, judicial officers, and administrators, allowing them to respond to the challenges of the twenty-first century. It is also a valuable resource for legal practitioners and judicial experts, shedding light on the role of the modern judge and the strategies they employ.